Implementation of PDCA and Seven Tools to Handle Obstacles in the KCl Screw Material Machine at PT Petrokimia Gresik - Muhammad Burhanuddin; Moh. Jufriyanto; Akhmad Wasiur Rizqi (Universitas Islam Raden Rahmat, Malang, 2025)
This study applies the Plan-Do-Check-Act (PDCA) method and the Seven Tools of Quality Control to address jamming issues in the screw machine handling KCl at PT Petrokimia Gresik. Frequent jams caused by wires and cement slurry led to downtime and production losses. PDCA was chosen for its systematic approach to problem-solving. In the Plan phase, check sheets and Pareto analysis identified wires (75%) and cement slurry (25%) as primary causes. The Do phase implemented modifications, including installing a handhole for cleaning and a drain to remove coarse materials. The Check phase showed zero jams and downtime in December 2023, a significant improvement from previous monthly downtime of up to 2 hours. The Act phase standardized these changes into operating procedures and included operator training to enhance raw material supervision. Results showed improved operational efficiency by an average of 1.5 hours monthly and eliminated downtime. This highlights the value of structured methodologies and teamwork between maintenance and operations. Future recommendations include using PDCA and Seven Tools as standard approaches for problem-solving across various machines and processes at PT Petrokimia Gresik.